Migratory Fishes of South America : Biology, Fisheries and Conservation Status - Carolsfeld, Joachim; Harvey, Brian; Ross, Carmen; Baer, Anton (Ottawa: International Development Research Centre and the World Bank, 2013)
Fish species that migrate within the great rivers of South America support important local fisheries but are little known outside their native range. This book, written specially for the World Bank and the International Development Research Centre, represents the first collection of the work of local scientific experts on these remarkable fish. The authors cover the Upper Parana, Paraguay-Parana, Uruguay and São Francisco basins in Brazil, as well as the Brazilian and Colombian Amazon. They discuss not only the principal migratory species and their fascinating relationship with the water cycle in the rivers and wetlands, but also the fisheries they support, and their often precarious conservation status.